Immunology - Roitt, Ivan; Brostoff Jinathan; Male David (Edinburgh, Mosby, 2001)
The Sixth Edition of "Immunology" brings this classic textbook bang up-to-date. 250 top-quality photographs and over 400 colour illustrations bring immunology to life. Case Studies have been added placing immunology in a clinical context. Expanded Critical Thinking, with detailed feedback test understanding and provide a useful revision tool. This book is part of an unsurpassed coordinated learning package.
Appendix 1-4, 435-443p.; Glossary 445-452p.; Index 465-480p.
Keywords: Immunology; Medicine